Cryptococcus laurentii fungemia in a patient with chronic kidney disease on hemodialysis - Lima, Rafael Siqueira; Rodrigues Marçal, João Victor (Journal of Health & Biological Sciences, 2024)
Introduction: Chronic Kidney Disease (CKD) is a relevant comorbidity from clinical and public health perspectives. Infections are an important cause of death in those patients. Although rare, fungal infections are increasing in incidence. Case report: a 45-year-old female patient with CKD due to systemic lupus erythematosus (SLE) was admitted to a tertiary hospital due to a bloodstream infection (BSI) caused by Cryptococcus laurentii. She received treatment with anidulafungin with good initial response but presented clinical and laboratory worsening after a few days, and the treatment was switched to amphotericin B. The hemodialysis access was changed. Chest tomography, echocardiogram, eye fundus examination, and cerebrospinal fluid study did not show changes. After 32 days of amphotericin B, the patient presented clinical improvement and was discharged to take oral fluconazole for three (3) months. Conclusion: BSI due to Cryptococcus laurentii is rare in patients on chronic hemodialysis with a high potential for complications. Physicians should have clinical suspicion for those infrequent infections infractions, and culture evaluation should always be performed. The diagnosis is still a challenge, as well as the therapeutic regimen.